Epidemiology and Molecular Characteristics of mcr-9 in Citrobacter spp. from Healthy Individuals and Patients in China - Xiaoyang Ju; Siheng Wang; Xuemei Yang; Weihua Han; Chang Cai; Yuchen Wu; Congcong Liu; Jiao Qian; Xiaofei Zhao; Xiang Qian; Qiaoling Sun; Rong Zhang; et al. (Microbiology Spectrum, 2022)
ABSTRACT With the globally prevailing carbapenemase-producing (CP) Citrobacter spp., polymyxin antibiotics have been reconsidered as one of the last-resort treatment options. Our study was conducted to investigate the prevalence of mcr-9 in Citrobacter species. From October to November 2021, 650 fecal samples and 215 Citrobacter isolates were collected from healthy individuals and infected patients, respectively. Isolates were screened for the presence of the mcr-9 gene by the PCR method. mcr-9-carrying strains were identified by matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry. Due to the susceptibility to colistin, Citrobacter spp. isolates were first induced to increase the expression of mcr-9 on China blue agar plates containing colistin and were then subjected to conjugation experiments. Whole-genome sequencing was performed on the Illumina NovaSeq PE150 system. The prevalence of mcr-9 in the Citrobacter genus from healthy guts and infected patients was 0.62% and 1.86%, respectively. In all mcr-9-positive strains, MICs of polymyxin B were observed at ≤2 μg/mL, displaying a nonresistant phenotype. As for conjugation experiments, only one isolate successfully transferred the mcr-9 gene to Escherichia coli C600. Whole-genome sequencing showed that eight mcr-9-positive Citrobacter isolates carried mcr-9 and genes encoding resistance to beta-lactam antibiotics, including blaCMY, blaDHA, blaSHV, blaTEM, and blaCTX-M. We also discovered that mcr-9 could be located on the pKPC-CAV1321 plasmid. Our study investigated the prevalence of mcr-9 in Citrobacter spp. in both healthy individuals and infected patients and described the carriage of mcr-9 on the pKPC-CAV1321 plasmid for the first time. IMPORTANCE The emergence of mcr homologues posed a serious threat to the therapeutic efficiency of polymyxin antibiotics. Citrobacter freundii is generally regarded as an opportunistic pathogen associated with a variety of nosocomial infections. In this study, we investigated the prevalence of mcr-9 in Citrobacter spp. isolates from healthy individuals and infected patients and highlighted the importance of the rational use of antibiotics. In addition, this epidemiological investigation is the first to describe the carriage of mcr-9 on plasmid pKPC-CAV1321 and confirms the horizontal transfer of this plasmid. Our research may shed new light on further studies of mcr-9 dissemination in humans.